3D geological modelling of the Renard 2 kimberlite pipe, Québec, Canada: from exploration to extraction - Lépine, Isabelle; Farrow, Darrell (Mineralogy and petrology, 2018)
The Renard 2 kimberlite pipe is one of nine diamondiferous kimberlite pipes that form a cluster in the south-eastern portion of the Superior Province, Québec, Canada and is presently being extracted at the Renard Mine. It is interpreted as a diatreme-zone kimberlite consisting of two Kimberley-type pyroclastic units and related country rock breccias, all cross-cut by coherent kimberlite dykes and irregular intrusives. Renard 2 has been the subject of numerous diamond drilling campaigns since its discovery in 2001. The first two geological models modelled kimberlite and country rock breccia units separately. A change in modelling philosophy in 2009, which incorporated the emplacement envelope and history, modelled the entire intrusive event and projected the pipe shape to depth allowing for more targeted deep drilling where kimberlite had not yet been discovered. This targeted 2009 drilling resulted in a > 400% increase in the volume of the Indicated Resource. Modelling only the kimberlite units resulted in a significant underestimation of the pipe shape. Current open pit and underground mapping of the pipe shape corresponds well to the final 2015 geological model and contact changes observed are within the expected level of confidence for an Indicated Resource. This study demonstrates that a sound understanding of the geological emplacement is key to developing a reliable 3D geological and resource model that can be used for targeted delineation drilling, feasibility studies and during the initial stages of mining.